Transanal TME – really needed? - Dapri Giovanni (Innovative Surgical Sciences, 2017)
In the last decade, thanks to natural orifice translumenal endoscopic surgery, the application of laparoscopy through the anus has gained interest from both research and clinical point of views. Therefore, an increased number of transanal procedures have been reported, from the resection of a large rectal polyp to total mesorectal excision, and for controlling perioperative complications like leak, bleeding, and stenosis. Currently, the most popular surgical trend remains transanal total mesorectal excision. In this article, the technique, advantages, and disadvantages are discussed.